Design of a Rumah Budaya in the Context of Preserving Karo Culture in Desa Lingga, Karo Regency, North Sumatra - Nasution, Putri Handayani; Ginting, Salmina Wati (Talenta Publisher, 2023)
The Siwaluh Jabu Traditional House is one of the cultural heritages from the ancestors of the Karo people from the past. This traditional house is located in Desa Lingga (Lingga Village), Karo Regency, North Sumatra, Indonesia. The interest of tourists in visiting this traditional house has made the local government make Desa Lingga a cultural village. Traditional houses and other cultural heritage symbolize the greatness of the Batak Karo ancestors in the past. Nevertheless, the